PENGARUH PERSEPSI DOWNLINE TENTANG KUALITAS JASA UPLINE PADA MULTI LEVEL MARKETING TIANSHI TERHADAP LOYALITAS DOWNLINE DI MALANG (Studi pada jaringan Akhmad Fidzan) - Devi Purnamasari (Jurnal Ilmiah Komunikasi Makna, 2014)
Good service quality dimensions will provide an incentivite to customers to establish a strong bond with company.Reverse poor service means the company’s reputation will go down, so the company leaders must know what the most influential variable on the dimension of service quality in a Multi Level Marketing company to rise the reputation of a company. A satisfaction who have received referrals effect on loyality, which it is suitable with statement Lam et.al (2002:31) who proved that service quality has an impact on satisfaction and satisfaction on loyalty.This study aims to identify and analyze the influence of service quality dimensions upline downline loyality either simultaneously or partially and to investigate and analyze the variables of service quality dimensions dominate the downline. An examination loyalty is done sub Stockists Uno Tianshi Business Center in Malang Jl.Griya Santa Malang by using a sample population of 60 respondents.The type of analysis is explanatory research with survey method. A technics of taking over a sampling using purposive sampling. A source premire data using the result of qestionaire and secondary data is literature and data from internet. An analysis implements used is multiple liniear regression.Result of multiple regression analyze is the dimension of service quality (X) consisting of physical evidence (X1),reliability (X2), responsiveness (X3), collateral (X4), and empathy (X5) is significant and simultaneous downline loyality (Y). While the effects is partially downline loyality (Y) just empathy variables(X5),while the four other variables that influence but do not significant. Except can also be shown that the variable of empathy (X5) is significantly dominant downline loyality (Y).Keywords: dimension of service quality, consisting of physical evidence, reliability, responsiveness, collateral, empathy and downline loyality.